IMPLEMENTASI STANDAR PELAYANAN KESEHATAN TERHADAP PASIEN PADA PUSKESMAS DI KABUPATEN KAMPAR - Das'at Zulhendra; Ardiansah Ardiansah; Iriansyah Iriansyah (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2022)
Abstract: Health Service Standards in Kampar Regency are very important in improving health-based development for communities throughout the country. In accordance with Permenkes 43 of 2019 concerning Puskesmas, it is hoped that they can implement health service standards for patients at the Kampar district health center. This study aims to determine the implementation of service standards at the puskesmas to patients and to review the legal aspects of responsibility for health services at the puskesmas. This research is normative juridical based on studies of legislation, books, various articles and electronic media that are closely related to health service standards at the Kampar District Health Center. For this reason, it is very necessary to have awareness and affirmation of regulations for health workers in providing health service standards for patients at the Kampar District Health Center in order to increase the degree of community welfare. Keywords: Services, Health Center, Kampar Abstrak: Standar Pelayanan Kesehatan di Kabupaten Kampar sangat penting dalam meningkatkan pembangunan berbasis kesehatan bagi masyarakat di seluruh wilayah tanah air. Sesuai dengan Permenkes 43 Tahun 2019 tentang Puskesmas sangat diharapkan bisa mengimplementasikan standar pelayanan kesehatan terhadap pasien di puskesmas kabupaten Kampar. Penelitan ini bertujuan untuk mengetahui implementasi standar pelayanan di puskesmas terhadap pasien dan meninjau aspek tanggung jawab dari sisi hukum bagi layanan kesehatan di puskesmas. Adapun penelitian ini bersifat Yuridis Normatif berdasarkan kajian dari perundang-undangan, buku-buku, berbagai artikel dan media elektronik yang erat kaitannya dengan standar pelayanan kesehatan di Puskesmas Kabupaten Kampar. Untuk itu sangat diperlukan adanay kesadaran dan penegasan terhadap peraturan bagi tenaga kesehatan dalam memberikan standar pelayanan kesehatan bagi pasien di puskesmas Kabupaten Kampar agar bisa meningkatkan derajad kesejahteraan masyarakat. Kata kunci: Pelayanan, Puskesmas, Kampar